2002
DOI: 10.3748/wjg.v8.i3.520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maotai liquor in inducing metallothioneins and on hepatic stellate cells

Abstract: Maotai liquor can increase metallothioneins in the liver and inhibit the activation of HSC and the synthesis of collagen in many aspects, which might be the mechanism that Maotai liquor interferes in the hepatic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…D-penicillamine, which blocks intra-and interchain crosslinking in the newly formed collagen molecules, was found to be ineffective on preventing the progression of hepatic fibrosis and was associated with a high incidence of serious side effects. Medicinally useful plants have made a significant contribution to current medical practice and traditional Chinese herbs are well known for their cheap prices and negligible side effects [31][32][33][34][35][36][37][38][39][40][41] . GbE is a well-known and inexpensive herb that has been used to improve blood circulation without ill effects for centuries in traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…D-penicillamine, which blocks intra-and interchain crosslinking in the newly formed collagen molecules, was found to be ineffective on preventing the progression of hepatic fibrosis and was associated with a high incidence of serious side effects. Medicinally useful plants have made a significant contribution to current medical practice and traditional Chinese herbs are well known for their cheap prices and negligible side effects [31][32][33][34][35][36][37][38][39][40][41] . GbE is a well-known and inexpensive herb that has been used to improve blood circulation without ill effects for centuries in traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In these varied ways, the physiological activity of HS cells is controlled by many factors. Recent reports also revealed a relationship between increased intrahepatic MT and suppression of hepatic fibrosis (Cheng et al, 2002(Cheng et al, , 2004, suggesting that increasing or decreasing the amount of MT protein could lead to HS cell activation. The immortal HS cell lines established in this study demonstrated varied sensitivity to heavy metals such as Cd and Hg.…”
Section: Discussionmentioning
confidence: 96%
“…However, the effect of MT on the induction of apoptosis by DMAA in vivo remains elusive. Furthermore, the perturbation of apoptosis has been thought to contribute to carcinogenesis either through enhanced initiation or progression [29][30][31][32][33][34][35][36][37][38] . In this study, the induction of apoptosis was detected by TUNEL in the lungs, livers and kidneys from both types of mice.…”
Section: Discussionmentioning
confidence: 99%
“…MTs, thiol-rich metal binding proteins, have been shown to be easily induced by oxidative stress and heavy metals and play an important role in homeostasis of essential metals, detoxication of heavy metals, scavenging reactive oxygen intermediates and preventing carcinogenesis as an endogenous defensive factor [10][11][12][13][14][15] . Especially to be mentioned, its capacity of scavenging hydroxyl and superoxide radicals is much more efficient than GSH, an established antioxidant [15] .…”
Section: Introductionmentioning
confidence: 99%